2011
DOI: 10.1002/cne.22608
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NPY Y2 receptor protein expression in the mouse brain. II. Coexistence with NPY, the Y1 receptor, and other neurotransmitter‐related molecules

Abstract: Neuropeptide Y (NPY) is widely expressed in the brain and its biological effects are mediated through a variety of receptors. We examined, using immunohistochemistry, expression of the Y2 receptor (R) protein in the adult mouse brain and its association with NPY and the Y1R, as well as a range of additional neurotransmitters and signaling-related molecules, which previously have not been defined. Our main focus was on the hippocampal formation (HiFo), amygdaloid complex, and hypothalamus, considering the known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 205 publications
(243 reference statements)
7
47
1
Order By: Relevance
“…The hippocampus is an important component of neuronal circuitry controlling anxiety-related behaviors and stress responses and seems to inhibit the HPA axis through glutamate-GABA connections (31). Previous studies have shown that Y1Rs are associated with glutamate-positive and NPYpositive neurons in hippocampal subregions, providing the anatomical basis for the Y1R-mediated modulation of glutamate and NPY release (32,33). Thus, we postulate that the selective inactivation of Y1Rs in principal excitatory neurons of hippocampus might stimulate HPA axis via the glutamatergic output.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is an important component of neuronal circuitry controlling anxiety-related behaviors and stress responses and seems to inhibit the HPA axis through glutamate-GABA connections (31). Previous studies have shown that Y1Rs are associated with glutamate-positive and NPYpositive neurons in hippocampal subregions, providing the anatomical basis for the Y1R-mediated modulation of glutamate and NPY release (32,33). Thus, we postulate that the selective inactivation of Y1Rs in principal excitatory neurons of hippocampus might stimulate HPA axis via the glutamatergic output.…”
Section: Discussionmentioning
confidence: 99%
“…Because we show that Y1 receptor activation has a greater effect than activation of the Y2 receptor on lipoprotein metabolism, it informs of potential structure-function relationships of the NPY-regulated neural circuitry involved. There is a reportedly close physical localization and apparent functional relationship between NPY Y1 and Y2 receptors in neurons found within the ARC, the lateral hypothalamic area, the dorsomedial hypothalamic nucleus, and the paraventricular nucleus (PVN), whereas the ventromedial hypothalamic nucleus (VMN) contains only Y1 receptor-positive neurons (60). Furthermore, a study by Chee et al (15) reports that NPY inhibits the excitatory (anorexigenic) outflow between the VMN and ARC POMC neural circuitry via the activation of the Y1 receptor subtype in the VMN.…”
Section: E1484 Cns Npy Receptor Subtypes Feeding and Vldl-tg Secretionmentioning
confidence: 98%
“…NPY affects a wide variety of physiological functions via the activation of a population of distinct G protein-coupled NPY receptor subtypes: Y1, Y2, Y4, and Y5 (29,35). All NPY receptor subtypes are expressed in the hypothalamus (18,60). The effects of NPY on feeding and energy homeostasis are thought to be mediated largely by hypothalamic Y1 and Y5 receptors (reviewed in Ref.…”
mentioning
confidence: 99%
“…Y 1 Rs are expressed on both BLA pyramidal and non-pyramidal neurons, where they are postsynaptically localized (Rostkowski et al, 2009;Stanic et al, 2011). A functional interaction between GABAergic and Y 1 Rs mediating transmission was first demonstrated in the cortical region (Kask et al, 1996) and, subsequently, in other brain regions, such as posterior hypothalamus (Naveilhan et al, 2001) and central and medial amygdala (Oberto et al, 2000(Oberto et al, , 2001) of mice.…”
Section: Introductionmentioning
confidence: 99%